Architecture for all: ageing & aged: a perspective from academia and practice in Malaysia - Mohd Nawawi, Norwina; Abdullah, Fadzidah; Abdul Majid, Noor Hanita; Abdul Rahim, Asiah; Abdul Rahim, Zaiton; Denan, Zuraini (2016)
Empathy in Architecture is not an option but remain a choice by most architects and architecture students as one of the factors in design considerations. According to WHO, more people (comparing with which duration) lives beyond world average life expectancy of 81years old and occurs in all society. This presentation aimed at capturing the facts of Ageing and Aged as natural phenomena of living for all humans and the need for architecture, as a noble profession, to address these needs as a second nature in design. Case studies of Malaysian scenario from a demographic profile, good and bad practices - through facilities by example and design guidelines provision are discussed and presented. As we aged, we realised how much we depend on the empathy of the present architecture to empower the ageing generation, some independence with dignity, and thus will not burden the next generation of our incapability. The future is indeed now and always.